K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 12 2016

\(P=\frac{x^2+2}{x^2+3}=1-\frac{1}{x^2+3}\ge1-\frac{1}{0+3}=\frac{2}{3}=dpcm\)

29 tháng 12 2016

\(\frac{\left(a+b\right)^2}{a^2-b^2}\)

\(=\frac{\left(a+b\right)^2}{\left(a-b\right)\left(a+b\right)}\)

\(=\frac{\left(a+b\right)}{\left(a-b\right)}\)

\(=\frac{2+3}{2-3}\)

\(=\frac{5}{-1}\)

\(=-5\)

29 tháng 12 2016

Cho a, b, c thỏa mãn:

1a+1b+1c=1a+b+c1a+1b+1c=1a+b+c

Chứng minh (a+b)(b+c)(c+a) =0

16 tháng 8 2017

mk cx đag hỏi câu đó